Aplikasi Pemberian Pakan Serta Kekeruhan Air Kolam Ikan Cupang Berbasis Nodemcu - A A Putra Hasibuan; T Syahputra; D Setiawan; J Halim (Jurnal MESIL (Mesin Elektro Sipil), 2021)
Keeping fish, especially betta fish, is a hobby that has been loved by many people from the past until now, because of the ease of maintenance and care. Feed is one of the important components in betta fish cultivation in determining fish growth. However, for people who have a fairly dense level of busyness at work, they will definitely feel a little difficult when they are going to leave the house, especially for a long time. The application of automatic scheduling of fish feeders in fish ponds using the Real Time Clock (RTC) module is considered quite appropriate because this RTC module can adjust the schedule of feeding fish according to the time we want. Then to detect the level of turbidity of the water, a photodiode sensor is used to determine the level of turbidity of the water through the light that is reflected to the photodiode sensor so that the betta fish can live more comfortably and not be stressed, and using the Internet Of Thing (IOT) to be monitored in real time via a smartphone that is connected to the NodeMCU ESP8266 by utilizing an internet signal.